Paraclinus walkeri Hubbs 1952 ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Paraclinus walkeri Hubbs, 1952. San Quintin Blenny. To 8.7 cm (3.5 in) TL (Rosales-Casián 2000). Bahía San Quintin, northern Baja California (Hubbs 1952). 1–10 m (3–33 ft) (min.: Personal communication: Scripps Institution of Oceanography Fish Collection, La Jolla, California; max.: Rosales-Casián 2000). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 199, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...